Litvinenko [videorecording (DVD)] - Kay, George (Screenwriter); Tennant, David, 1971-; Levieva, Margarita, 1980-; Blaev, Temirlan; Maskell, Neil, 1976-; Sloane, Barry, 1981-; Naudi, Sarah; Bonnar, Mark; Ivanir, Mark; Meadmore, Robert; Ryan, Daniel, 1968-; Meikle, Kayla; et al. (RLJ Entertainment, 2023)
Litvinenko, a former Russian spy dies in a London hospital, but not before naming his murderer. Poisoned with the deadliest substance known to man detectives dive into a high-stakes murder investigation. Can they find justice for Litvinenko's family?